A. Library preparation strategy: poly-A(+) RNAs are captured by complementarity to reverse transcription primer, then second strand is synthesized using random hexamers and handles for sequencing are attached through two rounds of PCR. B. Mapped read distribution by species and by biotype. C and D. Principal component analysis of mouse and T. gondii transcriptomes, respectively. E and F. Volcano plots of Live Toxoplasma-infected mouse and T. gondii time points, respectively. To calculate Log2(Fold change), every timepoint is compared to corresponding samples (either macrophage or Toxoplasma) before infection (t = 0 min). Most significant and most upregulated transcripts are labelled. Number of significantly (p ≤ 0.05) downregulated and upregulated genes for each time point is given in blue and red, respectively. In F, 24-hour time point, red dots mark ROP - Dominykas Murza (22676289) (2025)
A. Library preparation strategy: poly-A(+) RNAs are captured by complementarity to reverse transcription primer, then second strand is synthesized using random hexamers and handles for sequencing are attached through two rounds of PCR. B. Mapped read distribution by species and by biotype. C and D. Principal component analysis of mouse and T. gondii transcriptomes, respectively. E and F. Volcano plots of Live Toxoplasma-infected mouse and T. gondii time points, respectively. To calculate Log2(Fold change), every timepoint is compared to corresponding samples (either macrophage or Toxoplasma) before infection (t = 0 min). Most significant and most upregulated transcripts are labelled. Number of significantly (p ≤ 0.05) downregulated and upregulated genes for each time point is given in blue and red, respectively. In F, 24-hour time point, red dots mark ROP